2008
DOI: 10.1021/jp803105n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of Cationic and Anionic Surfactants in Mixed Monolayers and Aggregates

Abstract: The properties of anionic-rich and cationic-rich mixtures of CTAB (cetyltrimethylammonium bromide) and SDS (sodium dodecyl sulfate) were investigated with conductometry and surface tension measurements and by determining the surfactant NMR self-diffusion coefficients. The critical aggregate concentration (CAC), surface tension reduction effectiveness(gamma(CAC)), surface excess(Gamma(max)), and mean molecular surface area (A(min)) were determined from plots of the surface tension (gamma) as a function of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
89
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(101 citation statements)
references
References 52 publications
5
89
1
Order By: Relevance
“…Mixed micellization of cationic/anionic surfactants has attracted increasing interest over the past 20 years due to the strong synergism arising from the strong electrostatic attraction between the oppositely charged headgroups [36][37][38][39][40][41][42][43][44][45]. Usually the micellar compositions of the mixed cationic/anionic surfactants at cmc are nearly equimolar over a wide range of mixing ratios [46][47][48][49], the addition of inorganic salt has little or no effect on the cmc of these mixed cationic/anionic surfactant systems.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed micellization of cationic/anionic surfactants has attracted increasing interest over the past 20 years due to the strong synergism arising from the strong electrostatic attraction between the oppositely charged headgroups [36][37][38][39][40][41][42][43][44][45]. Usually the micellar compositions of the mixed cationic/anionic surfactants at cmc are nearly equimolar over a wide range of mixing ratios [46][47][48][49], the addition of inorganic salt has little or no effect on the cmc of these mixed cationic/anionic surfactant systems.…”
Section: Introductionmentioning
confidence: 99%
“…We found that, by using this model, we could explain the experimentally observed behavior in terms of the free energy contributions to mixed micelle formation. We investigated the adsorption properties of binary surfactant systems containing the cationic surfactant cetyltrimethylammonium bromide (CTAB) and the anionic surfactant sodium dodecyl sulfate (SDS) in aqueous solutions [20]. Also, we determined the mixed micelle and adsorption properties of binary surfactant systems containing the cationic and nonionic surfactants in the presence of various concentrations of sodium bromide [21].…”
Section: Introductionmentioning
confidence: 99%
“…The size, charge, and permeability of the catanionic vesicles can be further adjusted by varying the temperature, concentration, molar ratio, and chain length of the cationic and anionic surfactants 15 . Moreover, catanionic vesicles can efficiently encapsulate solutes and retain the molecules over long periods 16,17 .…”
Section: Introductionmentioning
confidence: 99%